A new species of Tiddergasilus Marques & Boeger, 2018 (Copepoda: Ergasilidae) from the gills of Astyanax lacustris (Lütken) (Osteichthyes: Characidae) in Brazil - Narciso, Rodrigo Bravin [UNESP]; Vieira, Diego Henrique Mirandola Dias [UNESP]; Silva, Reinaldo José da [UNESP] (Springer Nature, 2022)
A new parasitic copepod, Tiddergasilus bipartitusn. sp. (Copepoda, Ergasilidae), is described herein based on three adult females found attached to the gills of the yellow-tail lambari Astyanax lacustris (Lütken), sampled in Pardo River, municipality of Botucatu, São Paulo State, Brazil. Tiddergasilus bipartitusn. sp. was recognized as a new member of the monotypic genus Tiddergasilus Marques & Boeger, 2018 by having: antennule 6-segmented; maxillary basis armed with 2 terminal teeth and ornamented with multiple spinules; second and third leg both with endopod 3-segmented. The new copepod can be distinguished from its congener, Tiddergasilus iheringi (Tidd, 1942), by the morphology of the antennal claw, number of somites/segments in abdomen and fourth leg, and by the ornamentation of the first leg. This report expands the geographic distribution and diversity of fish species parasitized with Tiddergasilus spp. in Brazil. Moreover, it also represents the first report of an ergasilid species in the Pardo River. A list of diagnostic features for the Brazilian species of Ergasilus von Nordmann, 1832 is provided herein, in order to aid comparisons with the species of this complex genus.